Pengaruh Rasio Keuangan Terhadap Likuiditas Bank Umum Syariah Di Indonesia Periode 2015-2024 : Pendekatan Short Term Mismatch - Risma Wati; Gustika Nurmalia; Anggun Okta Fitri (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2026)
Liquidity represents a bank’s capacity to fulfill its short-term obligations using current assets that mature within one year. This measure is vital for ensuring financial stability and sustaining long-term profitability. This study examines the influence of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Return on Assets (ROA), and Operational Costs to Operating Income (BOPO) on liquidity, which is assessed through the Short Term Mismatch (STM) in Islamic Commercial Banks in Indonesia. A quantitative method is applied, utilizing secondary data from annual reports covering the 2015–2024 period. The population consists of all Islamic Commercial Banks registered with the Financial Services Authority (OJK) in 2024, with nine banks chosen as the sample using purposive sampling. The findings indicate that CAR positively and significantly affects STM, BOPO negatively and significantly affects STM, while NPF and ROA show no significant impact. Collectively, the four independent variables account for 54.33% of STM variability, with the remainder influenced by other factors beyond the model.The study suggests that enhancing capital adequacy and operational efficiency is essential for maintaining liquidity stability, and the results can inform the development of more effective liquidity management strategies.